Effect of internationalisation on balanced scorecard among Malaysian small and medium enterprises - Chong, Poh Ling; Ong, Tze San; Amalina Abdullah,; Choo, Wei Chong (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this paper is to identify the relationships between dimensions of internationalisation on balanced scorecard (BSC), among Malaysian small and medium enterprises (SMEs). Internationalisation covers the dimensions of knowledge, trust and commitment. Internationalisation can benefit the firm performance of SMEs in Malaysia which is measured using balanced scorecard, by increasing the involvement of SMEs in international business. A sample of 404 data was considered as the final sample size for this study. By using Structural Equation Modelling (SEM), the dimensions of internationalisation were observed to test the hypotheses. The results indicate that internationalisation as a whole does not have a role in the results of BSC among Malaysian SMEs. However, this also indicates that internationalisation is useful to reach the firm performance mostly in larger organisations because they require more strategic internationalisation to be more triumphant over their rivals which the larger organisations have. Furthermore, most SMEs in Malaysia are relatively new and being mostly family enterprises, these SMEs in Malaysia are more knowledgeable to perform domestic business. Therefore, this research conveys an understanding to the owners and managers to quickly achieve BSC results. Finally, this study brings some conclusions to the policy makers and regulators as well.